Digitalization in Vietnam Food & Beverage Industry - Thi Hoa, Do (Digital Repository of Theses, 2024)
The food and beverage (F&B) industry operates within a dynamic economic landscape, where product design must consistently adapt to evolving customer preferences. However, understanding these preferences poses a significant challenge due to the diverse experiences and changing demands across different periods, age groups, and regions. Consequently, gathering and processing customer data becomes arduous for F&B businesses, particularly in a complex market like Vietnam. This research endeavors to shed light on the potential of digitization in assisting Vietnamese F&B enterprises to effectively collect and process customer data. By leveraging the mixed research methods such as individual interviews and questionnaires with industry members, the study aims to comprehensively explore this subject matter, providing insights that bridge academic theory with practical applications within the Vietnamese F&B industry. While the interview was performed with 15 industrial experts, the questionnaire was administered to 80 employees in F&B enterprises. The study's findings offer valuable implications for managers seeking to refine their business strategies by aligning product development with customer needs. Findings show that the integration of digital technologies for data collection and processing in Vietnam's F&B sector marks a substantial and pivotal transformation. This shift is influenced by various factors, encompassing human resources, strategic initiatives, technological advancements, and legal frameworks. The consequences of this digital evolution are significant, leading to improved operational efficiency, heightened employee productivity, better financial performance, and increased adaptability to market demands among F&B enterprises. Nevertheless, it's crucial to recognize the accompanying challenges, including concerns regarding data security and the imperative for workforce training and development to fully capitalize on the benefits of digitalization. While the study provides valuable insights, it acknowledges its limitations, notably the reliance on a limited sample size for data collection. Consequently, the findings may not capture the full spectrum of customer data collection and processing methods within the F&B industry. Future research endeavors should aim to address this limitation by employing larger sample sizes to ensure a more comprehensive understanding of industry dynamics.